The role of nitric oxide in fusarium oxysporum f.sp. Cubense – banana interaction - Mohd Nasir, Nurul Najihah (2015)
Nitric oxide (NO) is involved in many physiological responses in plants including defense mechanism against biotic and abiotic stresses. NO is known to be an important signaling molecule in protein S-nitrosylation which involves modification of cysteine thiols to generate S-nitrosothiol (SNO). Protein extraction from Fusarium oxysporum f. sp. cubense (Foc)-banana root tissue was performed by using a modified TCA-acetone extraction method. Detection of S-nitrosylated proteins in the protein extract following biotin switch assay results in detection of a single band approximately at 52 kDa. Berangan banana seedlings which was treated with NO donor, nitrosogluthathione (GSNO) and NO scavenger, (2-(4-Carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide) cPTIO prior to inoculation with Foc indicated that disease progression in GSNO treated Berangan banana seedlings was delayed. On the other hand, disease progression was shown to be accelerated in cPTIO-treated Berangan banana seedlings. This study shows that NO plays important role in basal resistance against Foc.